2009
DOI: 10.1016/j.amepre.2009.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Athletic Identity to Child and Adolescent Physical Activity

Abstract: Background-Identity theorists maintain that domain-specific self-concepts help explain the differential investment of people's time and effort in various activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 33 publications
4
46
0
3
Order By: Relevance
“…Obesity was inversely associated with one PA outcome in boys, whereas being overweight, but not obese, was positively associated with girls’ participation in team sports. Previous studies have observed similar findings, 59 including greater PA in overweight relative to normal weight Hispanic girls. 60 The lack of a consistent relationship may reflect limitations of the self-report PA measures, the importance of energy intake, rather than energy expenditure, to BMI, and the limitations of BMI as a measure of adiposity in adolescents.…”
Section: Discussionsupporting
confidence: 70%
“…Obesity was inversely associated with one PA outcome in boys, whereas being overweight, but not obese, was positively associated with girls’ participation in team sports. Previous studies have observed similar findings, 59 including greater PA in overweight relative to normal weight Hispanic girls. 60 The lack of a consistent relationship may reflect limitations of the self-report PA measures, the importance of energy intake, rather than energy expenditure, to BMI, and the limitations of BMI as a measure of adiposity in adolescents.…”
Section: Discussionsupporting
confidence: 70%
“…Defined as “the degree to which an individual identifies with their athletic role”, athletic identity has been related to both positive and negative performance outcomes 127. From a positive dimension, a healthy athletic identity has been linked to stronger commitment to training and a greater focus on athletic goals 125,128. Likewise, strong athletic identities are associated with positive psychological outcomes such as enhanced body image, increased self-confidence, and decreased anxiety, as a result of intensive training and successful performance 128.…”
Section: Psychological Risks For Injury In Elite Athletesmentioning
confidence: 99%
“…50 Highlighting these pupils' capabilities in this specific aspect of fitness through testing could be a way to positively reinforce a specific "athletic identity." This construct predicts sports participation and PA levels independently of gender, body mass, ethnicity, 51 and perceived task competence. 52 Therefore, the inclusion of nonweight bearing strength and power tests increases the likelihood of good physical performances and is critical to ensuring that children across the range of BMI values receive positive feedback on physical performance.…”
Section: The Importance Of Muscular Fitness Testsmentioning
confidence: 99%